Karakteristik tulisan narasi fiksi berbahasa Arab mahasiswa penutur asli bahasa Indonesia - Nurhidayati, Nurhidayati (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This study is carried out to answer the research question: what are the characteristics of intrinsic elements, including plot, character, and setting, in Arabic fictitious narrative writing by Indonesian native-language students? This study is qualitative in nature. The approach used is socio-psycho-structural. The data are verbal and consist of: (1) fictitious narrative writing, (2) interview transcripts, and (3) field notes. The data on fictitious narrative writing were taken from the students’ portfolio of narrative fiction final tasks in the Writing Lecture 1 course. Interview transcripts and field notes from the teaching process were used to clarify and complete the data from the fictitious narrative writing. The data were analyzed using an interactive analysis method. Based on the findings, it can be concluded that: first, linear plot is the dominant plot in the students’ fiction writing; second, character naming and physiological description are dominant, with characters described through both direct and indirect description; and third, story setting is dominated by descriptive backgrounds focusing on location and time without psychological meaning.